Literature Review: Providing Exclusive Breast Milk to Babies During the Pandemic COVID-19 - Ayu Endang Purwati; Metty Nurherliyany; Rosidah Solihah; Selmi Nur Agisni (Nurul Ilmi : Journal of Health Sciences and Midwifery, 2023)
Introduction Breastfeeding is the best solution for babies and children, especially in a pandemic situation. Breast milk remains the best nutrition that can protect babies and toddlers from various diseases, including during the COVID-19 outbreak. Changes in breastfeeding patterns during the COVID-19 pandemic need to be understood by breastfeeding mothers, both those suspected of being infected with COVID-19 and mothers who choose not to breastfeed directly. Objective: The aim of this research is to review literature, articles, and research documents regarding providing exclusive breast milk to babies during the pandemic COVID-19. Method: The method used in writing this article is a review of research results related to providing exclusive breast milk to babies during the pandemic COVID-19. The type of data used is secondary data. The data sources in this literature review study were obtained by searching scientific research articles from 2021 to 2022 using data bases such as Google Scholar and Science Direct. Result: Mothers knowledge regarding providing exclusive breast milk to babies during the pandemic COVID-19 shows that there are still many who do not know the procedures for giving breast milk. Breastfeeding mothers have greater concerns during the pandemic regarding adequate protection for their children, especially when it comes to breastfeeding their babies. This creates problems for mothers by raising doubts or concerns about whether the mother's breast milk is still safe to give to her baby. Conclusion: Based on the results of the study, there is a significant increase in knowledge about exclusive breastfeeding during the COVID-19 period after being given socialisation. Suggestions for future researchers to examine the characteristics of mothers who provide exclusive breastfeeding during the COVID-19 pandemic.